Multidimensional perception of the concept “school excellence” - Fisher, Yael; Ben Simon, Batel (Frontiers in Education, 2024)
This research aims to conceptualize and define teachers' perception of school excellence (TPSE) and investigate the relationship between personal background, school role, organizational factors, and TPSE. The scale for TPSE was developed especially for this study. Elementary school teachers (N = 197) participated during the 2018-2019 academic year. Data were analyzed using two quantitative approaches: The facet theory approach was selected for its ability to conceptualize phenomena, and the Structural Equation Modelling (SEM) approach. The variables in the SSA map in the radial configuration form three concentric circles of conditional perceptions: personal understanding of excellence, the perception of excellence reflected by their surrounding society, and the perception of the concept in the Western world. The school excellence components were deployed in an angular form showing three elements: leadership and management, students' achievement-related excellence, and pedagogical excellence. The measure of fit coefficients indicated good results: RMSEA = 0.00, TLI = 1.00, CFI= 1.00, NFI= 0.88, df = 28, χ² = 27.95, p = .47The implications of the study findings can be helpful for schools that wish to examine their excellence rankings to improve performance and maintain a constant level of school excellence.